Cervico‐vaginal placental α‐macroglobulin‐1 combined with cervical length for the prediction of preterm birth in women with threatened preterm labor. (28th October 2019) - Radan, Anda‐Petronela; Aleksandra Polowy, Justyna; Heverhagen, Anneke; Simillion, Cedric; Baumann, Marc; Raio, Luigi; Schleussner, Ekkehard; Mueller, Martin; Surbek, Daniel
Abstract: Introduction: Preterm birth is a major cause of neonatal morbidity and mortality. There is an urgent need to accurately predict imminent delivery to enable necessary interventions such as tocolytic, glucocorticoid, and magnesium sulfate administration. We aimed to evaluate placental α‐macroglobulin‐1 as a new diagnostic marker in the prediction of preterm birth. Material and methods: We performed a prospective observational trial in women with intact membranes between 24 +0 and 36 +6 weeks of gestation. We included both women with and without threatened preterm labor symptoms. We evaluated the test performance of placental α‐macroglobulin‐1 measurements in cervicovaginal fluid regarding three different presentation‐to‐delivery intervals: ≤2, ≤7, ≤14 days. In addition, we calculated placental α‐macroglobulin‐1 performance in combination with other prognostic factors such as ultrasonographic cervical length measurements. Results: We included 126 women in the study. We detected high specificity (97%‐98%) and negative predictive value (89%‐97%) for placental α‐macroglobulin‐1 at all time intervals. We assessed placental α‐macroglobulin‐1 in combination with cervical length measurements (≤15 mm) in the sub‐group of women presenting with threatened preterm labor symptoms (n = 63) and detected high positive predictive values (100%) for 7‐ and 14‐day presentation‐to‐delivery intervals. Conclusions: Our study provides evidence that placental α‐macroglobulin‐1 testing in cervicovaginal fluid, in combination with cervical length measurements, accurately predicts preterm birth in women with preterm labor symptoms. This novel test combination may be used clinically to triage women presenting with threatened preterm labor, avoiding overtreatment and unnecessary hospitalizations.